(untitled) (Journal of Engineering, 2013)
Modeling the microclimate of a greenhouse located in Baghdad under its weather conditions to calculate the heating and cooling loads by computer simulation. Solar collectors with a V-corrugated absorber plate and an auxiliary heat source were used as a heating system. A rotary silica gel desiccant dehumidifier, a sensible heat exchanger, and an evaporative cooler were added to the collectors to form an open-cycle solar assisted desiccant cooling system. A dynamic model was adopted to predict the inside air and the soil surface temperatures of the greenhouse. These temperatures are used to predict the greenhouse heating and cooling loads through an energy balance method which takes into account the soil heat gain. This is not included in conventional methods. The results showed satisfactory agreement with published papers. Also, the results of heating and cooling loads obtained revealed good agreement with those obtained from conventional methods when the soil heat gain is included. Two identical collectors in series of total area of 5.4m2 were employed as a heating system which provides an outlet air temperature of 30 o C at air mass flux of 0.06 kg/s.m2 at midday in January. While, a 65 oC outlet air temperature was achieved for the same mass flux at midday in August. The desiccant cooling system was operated in five operating modes; the ventilation mode and four recirculation modes with 20%, 50%, 70%,and 90% recirculation. The simulation results showed that a regeneration temperature of 60-70 o C is satisfactory for a cool supply air temperature of about 19.5 o C. Also, it was noted that 20-30 % recirculation of return air would result in suitable indoor greenhouse conditions for most periods of system operation. In addition, the coefficient of performance COP of the system was high compared with the conventional vapor compression systems.